Hubungan Hasil Tangkapan Ikan Tuna Selama Februari-Maret 2016 dengan Konsentrasi Klorofil-a dan SPL dari Data Penginderaan Jauh Di Perairan Selatan Jawa – Bali - I Made Ekayana; I Wayan Gede Astawa Karang; Abd. Rahman As-syakur; Irwan Jatmiko; Dian Novianto (Journal of Marine and Aquatic Sciences, 2017)
Indonesia waters are fertile waters marked by the existence of Regional Fisheries Management (WPP), one of them is WPP 573 in Southern Java. One of the biggest fish catch sectors in Indonesia is tuna fisheries. Distribution of tuna in Indonesia waters affected by Sea Surface Temperature (SST) and chlorophyll-a. The aims of this study is to analyze the distribution of chlorophyll-a and SST in the water of South Java - Bali using AQUA MODIS satellite through data in-situ, to know the accuracy of SST Ground Truth and SST imagery satellite and to find the relationship between chlorophyll-a and SST with catches tuna in the water of South Java - Bali. SST data and chlorophyll-a were obtained through remote sensing technology and the catches of tuna was obtained by in-situ. The methods used were polynomial regression analysis, regression linear analysis and correlation analysis to determine the relationship of these parameters, found strong correlation between SST Ground Truth and SST imagery satellite R= 0,61. The distribution of oceanographic parameters (SST and chlorophyll-a) in the water of South Java - Bali seemed volatile and these condition also seemed less affected catches of tuna. Found low inverse correlation SST with catches of tuna amounted to R = -0.34 and low correlation with the chlorophyll-a with catches of tuna amounted to R = 0.28.